Drug utilization and cost in a Medicaid population: A simulation study of community vs. mail order pharmacy - Seoane-Vazquez Enrique; Valluri Satish; Rodriguez-Monguio Rosa; Szeinbach Sheryl L (BMC, 2007)
Abstract Background Outpatient drugs are dispensed through both community and mail order pharmacies. There is no empirical evidence that substitution of community pharmacy with mail order reduces overall drug expenditures. The need for evaluating the potential effects on utilization and costs of the possible extension of mail order services in Medicaid provides the rationale for conducting this study. This study compares drug utilization and drug product cost in community vs. mail order pharmacy dispensing services in a Medicaid population. Methods This study is a retrospective cohort study comparing utilization and cost patterns in community vs. mail order pharmacy. A simulation model was employed to assess drug utilization and cost in mail order pharmacy using community pharmacy claim data. The model assumed that courses of drug therapy (CDT) in mail order pharmacy would have utilization patterns similar to those found in community pharmacy. A 95% confidence interval surrounding changes in average utilization and average cost were estimated using bootstrap analysis. A sensitivity analysis was performed by varying drug selection criteria and supply, fill point, and medication possession ratio (MPR). Sub-analyses were performed to address differences between mail order and community pharmacy related to therapeutic class and dual-eligible patients. Data for the study derived from pharmacy claims database of Ohio Medicaid State program for the period January 2000-September 2004. Drug claims were aggregated to obtain a set of CDTs representing unique patient IDs and unique drug products. Drug product cost estimates excluded dispensing fees and were used to estimate the cost reduction required in mail order to become cost neutral in comparison with community pharmacy. Results The baseline model revealed that the use of mail order vs. community pharmacy would result in a 5.5% increase in drug utilization and a 5.4% cost reduction required in mail order to become cost neutral. Results from Ohio Medicaid drugs for chronic use revealed a 5.1% increase in utilization and a 4.9% cost reduction required to become cost neutral in comparison with community pharmacy. Conclusion The results of the simulation model indicate that mail order pharmacy increases drug utilization and can also increase drug product cost if the cost per unit is not reduced accordingly. Prior consideration should be given to the patient population, day-supply, disease, therapy, and insurance characteristics to ensure the appropriate use of mail order pharmacy services.